Correlation of Inter-Ictal EEG Localization with Semiology and MRI in Symptomatic Focal Epilepsies - Sawsan AlBaazi; Akram Al-Mahdawi (Academic Journal of Clinicians, 2022)
Analysis of seizure semiology may provide a valuable information on the seizure onset zone and can be determined by history or video records of ictal event. Seizure semiology as a localizing tool could have some limitations and pitfall including inter-rater variability, therefore, we tried to assess the accuracy of basic level inter-ictal EEG in comparison to MRI to identify epileptiform changes and localization of epileptogenic lesions in less time and cost. Hence, A cross-sectional study conducted at the Epilepsy Clinic in Baghdad Teaching Hospital / Medical City during 2017 – 2018, included 70 patients referred for evaluation of recurrent seizures. We found that Basic level inter-ictal EEG with partial sleep deprivation can be used in localization and tracking of epileptogenic pathways, and the concept of being discordant from semiology should have a crucial attention, as previously suggested that the irritative zone correlate more accurately with epileptogenic zone.